PERAN PESANTREN SEBAGAI LEMBAGA PENDIDIKAN ISLAM DI INDONESIA - Asniah, Asniah; Evi, Fitaulifia; Rijal, Pahlevi (ILJ: Islamic Learning Journal, 2024)
This research aims to explore and analyze the role of Islamic boarding schools as Islamic educational institutions in Indonesia. Islamic boarding schools, as traditional Islamic institutions, have a long and deep history of providing religious education to the younger generation. In the context of pluralistic Indonesia, Islamic boarding schools play an important role in maintaining Islamic values, teaching religious teachings, and producing Muslim cadres who have a deep understanding of Islam. The approach applied in this study is a qualitative approach using the literature study method. The findings from this research indicate that Islamic boarding schools act as Islamic educational institutions that provide instruction, education, guidance and spread the teachings of the Islamic religion. The mission of Islamic boarding school education is to form an Islamic character that involves faith and devotion to Allah Sub??nahu Wa Ta'?lâ, respectful behavior, positive contribution to society, and service to the people (khadim al-umma?). Apart from functioning as educational institutions, Islamic boarding schools also act as centers of resistance to colonialism, locations for scientific research and development, training places, and community development institutions, which also have a significant role in preserving culture.